Spontaneous event of mitochondrial DNA mutation, A3243G, found in a family of identical twins. (April 2013) - Harihara, Shinji; Nakamura, Kennichi; Takubo, Kaiyo; Takeuchi, Fujio
<x xml:space="preserve">Abstract</x> A mutation in mitochondrial DNA (mtDNA) A3243G is an important cause of some serious mitochondrial diseases, and maternal inheritance of the mutation has been reported. In order to investigate the heredity of the mutation, we measured the ratio of the mutated mtDNA molecule among 32 families of identical twins. Both twins from one family showed 20.16% and 18.49% mutated molecules, and the level is significantly high in comparison with members of other families and control subjects (0.23–0.86%). Their parents, however, showed normal level of mutated molecules (0.70% and 0.66%). The high-level mutation of the twins may be due to a spontaneous event, which occurred during development of germ line of their mother, or oogenesis of their mother, or during early stage of their development.